Transparent chiral polymers for optical applications - Pujari, N. S.; Kulkarni, M. R.; Large, M. C. J.; Bassett, I. M.; Ponrathnam, S. (Journal of Applied Polymer Science, 2005)
Optically active chiral polymers and copolymers of cholesteryl methacrylate have been studied for use in optical applications including plastic optical fibers. Homopolymers of chiral cholesteryl methacrylate with differing molecular weights and copolymers with methyl methacrylate were synthesized by free-radical copolymerization in tetrahydrofuran using azobisisobutyronitrile at 67 degrees C for 26 h. All polymers were characterized for molecular weight, glass-transition temperature, optical rotation, transparency, and refractive index and solution blended to test for compatibility with poly(methyl methacrylate). Such chiral materials are of particular interest because they offer useful polarization properties without requiring bulk orientation of the molecules. This makes it possible to produce low cost optical elements such as circularly birefringent or circularly polarizing optical elements with potential applications in polarization manipulations and sensing. (c) 2005 Wiley Periodicals, Inc.
Keywords: chiral; cholesteryl methacrylate; optically active; plastic optical fiber; poly(cholesteryl methacrylate); poly(cholesteryl methacrylate-co-methyl methacrylate)

Novel beaded polymers from telechelic methacrylic ether esters - Pujari, N. S.; Trivedi, J.; Ingavle, Ganesh C.; Ponrathnam, S. (Reactive & Functional Polymers, 2006)
A series of telechelic dimethacrylic ether-esters (MEE) were prepared by solventless reaction of alpha,omega-dihydroxy poly(oxytetramethylene) (polytetrahydrofuran, PTHF) with phthalic anhydride and glycidyl methacrylate (GMA). MEE was polymerized with GMA as well as GMA-ethylene dimethacrylate (EGDM) to form porous beads. The terpolymer beads were observed using optical microscopy and SEM and characterized for internal pore volume, equilibrium volume-swelling ratio and dimethyl formamide and aqueous buffer regain. The morphology of the beads was dictated by the mole fraction and molecular weight of MEE in the feed. Porosity was found to increase with increase in molecular weight of MEE. Thus, porosity as high as 49%, 50% and 55% was observed with MEE of molecular weights 1580, 2580 and 3480, respectively. At a specific terpolymerization feed ratio of monomers, the terpolymers formed transform from gel like structure into a macroporous one, with increase in molecular weight of MEE. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: ether-ester dimethacrylates; macroporous; Pore size distribution; porosity; telechelics

Poly(urethane methacrylate-co-glycidyl methacrylate)-supported-polypropylene biphasic membrane for lipase immobilization - Pujari, N. S.; Vaidya, Bx; Bagalkote, S.; Ponrathnam, S.; Nene, Sanjay (Journal of Membrane Science, 2006)
Polypropylene (PP) was hydrophilized by coating followed by UV curing of a blend of 2-hydroxyethyl methacrylate (HEMA) terminated polyurethane prepolymer and glycidyl methacrylate (GMA). This allows formation of a hydrophobic membrane with increased surface hydrophilicity, biocompatibility and stability. Candida rugosa lipase (CRL) was covalently immobilized on this membrane using 5% glutaraldehyde as a crosslinking agent for post immobilization stabilization of enzyme on membrane. The membrane obtained was placed in a batch membrane reactor where a model esterification of oleic acid with octanol was studied. Under optimum conditions, the biocatalytic membrane gave a specific activity of 796.27 units/mg and 90.26% activity yield. Moreover, there was 85. 10% retention of specific activity. The biocatalytic membrane was observed to retain about 84.23% of its synthetic activity after six cycles. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Candida rugosa lipase; Enzyme immobilization; membrane bioreactor; urethane methacrylate

Thermotropic behavior of lithocholic acid derivative linked hydroxyethyl cellulose - Shaikh, V. A. E.; Maldar, Noormahamad N.; Lonikar, Shrikant Vitthal; Rajan, C. R.; Ponrathnam, S. (Journal of Applied Polymer Science, 2006)
Various mesogenic lithocholic acid (LA) derivatives [3-acetyl LA (LAAC); 3-propionyl LA (LAP), 3-cinnamoyl LA (LACin); 3-benzoyl LA (LAB), 3-(4-nitrobenzoyl) LA (LANB); and methyl-3-(3-carboxypropionyl) LA, i.e., LA methyl ester monosuccinate (LAMeMS)] were reacted with hydroxyethyl cellulose (HEC) to obtain a series of LA derivatives of HEC. These polymers were characterized by the mesogen content, 1.1, differential scanning calorimetry, and hot-stage coupled polarizing optical microscopy. The degree Of Substitution (DS) ranged from 0.27 to 1.11. Polymers HEC-LAB (DS = 1.11), HEC-LANB (DS = 0.80), HEC-LACin (DS = 0.76), and HEC-LAP (DS = 0.27) exhibited a mesophase on heating whereas HEC-LAB also showed a mesophase on cooling. The other polymers HEC-LAAC (DS = 0.89) and HEC-LAMeMS (DS = 0.36) did not reveal mesophase formation with either heating or cooling. It is observed that the formation of a mesophase is affected by the type of mesogen that is used rather than the mesogen content of the polymer. (c) 2006 Wiley Periodicals, Inc.
Keywords: hydroxyethyl cellulose; lithocholic acid; thermotropic

Immobilization of mushroom polyphenol oxidase on poly(allyl glycidyl ether-co-ethylene glycol dimethacrylate) macroporous beaded copolymers - Vaidya, Bhalchandra K.; Karale, Abhijeet J.; Suthar, Hitesh K.; Ingavle, Ganesh C.; Pathak, Tara Sankar; Ponrathnam, S.; Nene, Sanjay (Reactive & Functional Polymers, 2007)
Functional, macroporous, beaded copolymers containing epoxy groups were synthesized for immobilization of polyphenol oxidase (PPO) from edible mushroom (Agaricus bisporus). The effect of incorporation of two different sets of monomers such as glycidyl methacrylate (GMA) and allyl glycidyl ether (AGE) and the effect of cross-linking agent ethylene glycol dimethacrylate (EGDM) with varying cross-link densities on binding and expression of mushroom PPO activity were studied. The effect of porogen viz. cyclohexanol and hexanol on PPO immobilization was studied. AGE copolymers with hexanol as a porogen were found to give higher binding and expression of PPO activity than GE polymers. Crosslinking of amino groups of enzyme with 5% glutaraldehyde for 6 h gave a stable binding of PPO on AGE-75(Hex) polymer with storage half-life of approximately 25 days. Under optimum conditions, AGE-75(Hex) polymer gave 70.3% of activity yield while percent retention of PPO activity was found to be 83.5%. Immobilized PPO showed a broader pH, higher temperature and excellent storage stability. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: cross-linking agent; Enzyme immobilization; Epoxy-activated support; mushroom PPO

Spinning wave motion in frontal polymerization - Inamdar, Satish R.; Pujari, N. S.; Karimi, I. A.; Ponrathnam, S.; Tayal, R. K.; Kulkarni, B. D. (Chemical Engineering Science, 2007)
We present a mathematical model describing dynamics of spinning waves which propagate during frontal polymerization reaction taking place in a cylindrical reactor tube. The self-organization of spatio-temporal solution of wave equations due to interplay between thermal diffusion and kinetics gives rise to pattern formation. We begin with a fundamental equation of motion of radial coordinate after defining an asymptotic phase for spinmode. The motion is analyzed near a critical (Hopf) point and a perturbation solution is used to obtain patterns for a case of preparation of poly(2-hydroxyethyl methacrylate) (PHEMA) via frontal polymerization reaction. The model uses the distance as seen in photograph taken using scanning electron microscope (SEM) from which motion begins around core of spiral and calculates pitch of spiral which matches closely with experimental observation in micrograph. Also the model predicts qualitatively the ramp wave and spiral wave motion as observed under SEM. Both these results are reported in open literature for the first time to our best knowledge. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: frontal polymerization; spinning wave; spiral motion; wave dynamics

Immobilization of Candida rugosa lipase on poly(allyl glycidyl ether-co-thylene glycol dimethacrylate) macroporous polymer particles - Vaidya, Bhalchandra K.; Ingavle, Ganesh C.; Ponrathnam, S.; Kulkarni, B. D.; Nene, Sanjay N. (Bioresource Technology, 2008)
Macroporous polymer particles containing surface epoxy groups were synthesized for immobilization of Candida rugosa lipase (CRL). The effect of incorporation of two different sets of monomers [allyl glycidyl ether (AGE) and glycidyl methacrylate (GMA)] and the effect of crosslinking density on immobilization of lipase were studied. AGE-co-EGDM polymers gave higher binding and expression of lipase than GMA-co-EGDM polymers. Optimization of immobilization parameters was done with respect to immobilization time and enzyme loading. Amongst AGE-co-EGDM polymer series, AGE-150 polymer found to give maximum lipase activity yield and therefore evaluated for temperature, pH and storage stability. Under optimum conditions, AGE-150 polymer gave 78.40% of activity yield. Immobilized lipase on AGE-150 showed a broader pH, higher temperature and excellent storage stability. (C) 2007 Published by Elsevier Ltd.
Keywords: Candida rugosa lipase; Enzyme immobilization; Epoxy-activated support

Arthrobacter sp lipase immobilization for preparation of enantiopure masked beta-amino alcohols - Chaubey, Asha; Parshad, Rajinder; Gupta, Pankaj; Taneja, Subhash C.; Qazi, Ghulam N.; Rajan, C. R.; Ponrathnam, S. (Bioorganic & Medicinal Chemistry, 2009)
Recent reports on immobilization of lipase from Arthrobacter sp. (ABL, MTCC 5125; IIIM isolate) on insoluble polymers have shown altered properties including stability and enantioselectivity. Present work demonstrates a facile method for the preparation of enantiopure beta-amino alcohols by modulation of ABL enzyme properties via immobilization on insoluble as well as soluble supports using entrapment/covalent binding techniques. Efficacies of immobilized ABL on insoluble supports prepared from tetraethylorthosilicate/aminopropyltriethoxy silane and soluble supports derived from copolymerization of N-vinyl pyrrolidone-allylglycidyl ether (ANP type)/N-vinyl pyrrolidone-glycidyl methacrylate ( GNP type) for kinetic resolution of masked beta-amino alcohols have been studied vis-a-vis free ABL enzyme/wet cell biomass. The immobilized lipase on different insoluble/soluble supports has shown 21 - 110 mg/g protein binding and 30 - 700 U/g activity for hydrolyzing tributyrin substrate. The findings have shown a significant enhancement in enantioselectivity (ee 99%) vis-a-vis wet cell biomass providing ee 70-90% for resolution of beta-amino alcohols. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Arthrobacter sp lipase; beta-Aminoalcohol; Enantioselectivity; Immobilization; soluble polymer

Synthesis and photopolymerization kinetics of linear alicyclic urethane acrylate macromonomer in presence of reactive diluents - Harikrishna, Reghunathan; Bhosle, Sonali Madhavrao; Ponrathnam, S.; Rajan, C. R. (Journal of Materials Science, 2011)
This study deals with the photopolymerization of a macromonomer in the presence of reactive diluents using Photo Differential Scanning Calorimetry or Photo DSC. The kinetic profiles of these systems showed that the rate of photopolymerization rapidly increases at very early stages of the reaction. The rate of reaction was further found to increase with the addition of crosslinking agents. The addition of trifunctional crosslinking agent to the macromonomeric formulation resulted in a higher polymerization rate and conversion than that of a difunctional crosslinking agent. From the heat flow profiles, the kinetic parameters such as induction time, time to attain peak maximum, rate of maximum polymerization, and final conversion were noted for all the formulations. The initiation of photopolymerization was found to depend on the functionality while the in situ viscosity controlled the time scale for reaction diffusion which resulted in varying levels of conversions. Other parameters such as effect of temperature and concentration of photoinitiator on photocuring kinetics are also discussed.

Photopolymerization kinetics of 2-phenylethyl (meth) acrylates studied by photo DSC - Ghorpade, Ravindra V.; Bhosle, Sonali Madhavrao; Ponrathnam, S.; Rajan, C. R.; Chavan, Nayaku; Harikrishna, Reghunathan (Journal of Polymer Research, 2012)
The present work deals with the photopolymerization of 2-phenylethyl (meth)acrylates and estimation of their kinetic parameters. Formulations were made by independently homogenizing the monomers with photoinitiators of two different classes. Two different compositions of photoinitiators were used to study the effect of concentration of photoinitiator on cure kinetics. These compositions obtained were tested for photo curing performance using differential photocalorimetry (DPC) or photo DSC under polychromatic radiation. The heat flow against time was recorded for all formulations under isothermal conditions and the rates of polymerization as well as the percentage conversions were estimated. It was observed that due to a longer timescale for reaction diffusion, the methacrylate formulations showed a higher conversion than acrylate formulations. Other parameters such as induction time, maximum rate and conversion attained as well as the time to attain peak maximum were noted. The photopolymerization and kinetic estimations of the formulations including evaluation of kinetic models are discussed.
Keywords: Bimolecular termination model; Photo DSC; Photopolymerization; Variable autocatalytic model

Poly(allyl glycidyl ether-co-ethylene glycol dimethacrylate) copolymer beads as support for covalent immobilization of L-aminoacylase - Vaidya, Bhalchandra K.; Ingavle, Ganesh C.; Ponrathnam, S.; Nene, Sanjay N. (Reactive & Functional Polymers, 2012)
Porous epoxy-activated copolymer beads were synthesized as support for the covalent immobilization of Aspergillus melleus L-aminoacylase. Here, a series of copolymer bead were synthesized using either glycidyl methacrylate (GMA) or ally] glycidyl ether (AGE) as monomer units and ethylene glycol dimethacrylate (EGDM) as cross-linking agent. The effect of monomer used and the effect of amount of cross-linking agent on covalent immobilization of aminoacylase were studied. Furthermore, the effect of porogen on immobilization of aminoacylase was also evaluated. AGE-co-EGDM copolymer beads gave higher binding of aminoacylase than GMA-co-EGDM copolymer beads. AGE-co-EGDM copolymer beads synthesized with lauryl alcohol as porogen and having 150% cross-linked density (i.e. AGE-(L)-150) gave maximum enzyme binding. Under optimum conditions, AGE-(L)-150 copolymer beads gave about 130 U/g of aminoacylase activity which corresponds to 72.24% of activity yield. Immobilized aminoacylase showed a broader pH, higher temperature and extended storage stability. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Enzyme immobilization; Epoxy-activated support; L-Aminoacylase

Photopolymerization of bis-aromatic and alicyclic based solid urethane acrylate macromonomer in the presence of large excess of reactive diluent Kinetics and modeling - Harikrishna, Reghunathan; Ponrathnam, S.; Rajan, C. R.; Tambe, S. S. (Journal of Thermal Analysis and Calorimetry, 2013)
A solid urethane acrylate macromonomer with bis-aromatic as well as alicyclic moieties was synthesized and the kinetics of photopolymerization reactions were studied in the presence of varying concentration of photoinitiator and large excess of reactive diluent using photo DSC. The studies show that the rate of maximum polymerization was found to increase with increase in concentration of photoinitiator while a decrease was observed by an increase in temperature. The final conversion showed a decrease at highest isothermal condition due to vitrification. Estimation of kinetic parameters including applicability of autocatalytic and modified autocatalytic models were investigated by nonlinear regression. It was observed that the modified models gave a better fit with the experimental data and kinetic parameters showed a decrease with increase in temperature and an increase with increase in concentration of photoinitiator.
Keywords: Autocatalytic model; kinetics; Levenberg-Marquardt method; Photopolymerization

Photopolymerization kinetics of bis-aromatic based urethane acrylate macromonomers in the presence of reactive diluent - Harikrishna, Reghunathan; Ponrathnam, S.; Rajan, C. R. (Progress in Organic Coatings, 2014)
The present work deals with the photopolymerization of bis-aromatic based urethane acrylate macromonomers in the presence of excess end capping agent as reactive diluent and estimation of their kinetic parameters. Formulations were made by independently homogenizing the macromonomers with photoinitiators of three different classes. Three different compositions of photoinitiators were used to study the effect of concentration of photoinitiator on cure kinetics. These compositions obtained were tested for photo curing performance using photo DSC under polychromatic radiation. The heat flows against time were recorded for all formulations under isothermal condition and the rates of polymerization, peak maximum times as well as the percentage conversions were estimated. It was observed that due to a longer timescale for reaction diffusion, formulations with macromonomer containing propoxylated backbone showed higher conversions than the corresponding ethoxylated analogue. The photopolymerization and kinetic estimations of the formulations including evaluation of kinetic model are discussed. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Bimolecular termination model; kinetics; Macromonomer; Photopolymerization

Photopolymerization of high internal phase emulsions based on 2-ethylhexyl (meth)acrylates and ethylene glycol dimethacrylate - Harikrishna, Reghunathan; Shaikh, A. W.; Ponrathnam, S.; Rajan, C. R.; Bhongale, Sunil Sitaram (Designed Monomers and Polymers, 2014)
Photopolymerization of high internal phase emulsions based on 2-ethylhexyl (meth)acrylates and ethylene glycol dimethacrylate was carried out in presence of low concentration of different photoinitiators. The stable emulsions obtained by mixing with individual photoinitiators were subjected to low-intensity photopolymerization under UV-Visible lamp. Identical samples were irradiated for differing periods ranging from 2 to 10min at an interval of 2min. The percentage conversions of each monomer in the compositions with respect to the time of irradiation were determined using gas chromatography. It was observed that the formulations containing IRGACURE 819 showed the highest conversion while that containing IRGACURE 2959 showed the least conversion. The former showed high conversion due to the proximity of the absorption maxima of photoinitiator to the major emission line of mercury spectrum at 365nm while the latter showed least conversion due to non-availability of major absorption maxima within the irradiation range.
Keywords: (meth)acrylates; high internal phase emulsion; Photopolymerization; residual monomer analysis

Reaction kinetics and modeling of photoinitiated cationic polymerization of an alicyclic based diglycidyl ether - Harikrishna, Reghunathan; Ponrathnam, S.; Tambe, S. S. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 2014)
Photoinitiated cationic polymerization of cycloaliphatic diepoxides had received tremendous attention, while studies with lesser polymerizable diglycidyl ethers are comparatively less reported. The present work deals with the photoinitiated cationic polymerization of cyclohexane dimethanol diglycidyl ether followed by estimation of kinetic parameters. The effects of concentration of photoinitiator and temperature on curing performance were studied using photo differential scanning calorimeter or photo DSC with polychromatic radiation. It was observed that the rate of polymerization as well as ultimate conversion increased with increasing concentration of photoinitiator and temperature. The influences of gelation as well as diffusional restrictions have remarkable effect on cure performance. The kinetic parameters as per autocatalytic kinetic model were studied by Levenberg-Marquardt nonlinear regression method instead of conventional linear method for obtaining more accurate values of apparent rate constant. It was observed that the model fits with data from initial stages to almost towards the end of the reaction. The activation energy was found to be higher than the values reported for more reactive cycloaliphatic diepoxides. The value of pre-exponential factor increased with increase in activation energy showing influence of gelation at early stages of reaction. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Autocatalytic model; kinetics; Levenberg-Marquardt method; Photopolymerization

Ambient temperature photocopolymerization of tetrahydrofurfuryl methacrylate and isobornyl methacrylate: reactivity ratios and thermal studies - Rajdeo, K. S.; Ponrathnam, S.; Pardeshi, S.; Chavan, Nayaku; Bhongale, Sunil Sitaram; Harikrishna, Reghunathan (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2015)
Photocopolymerization of heterocyclic monomer namely, tetrahydrofurfuryl methacrylate with bulky bicyclic monomer, isobornyl methacrylate with different feed ratios was carried out in bulk with low concentration of an -hydroxyl ketone based photoinitiator. The ambient temperature photocopolymerization was carried out by using a UV-Visible lamp with fixed low intensity of 0.4mW cm(-2) for a period of 6min. The residual monomer remained in the polymerization process were determined by using gas chromatography. The reactivity ratio values for the two monomers were calculated from the copolymer composition data by using Fineman-Ross, Kelen-Tudos, Extended Kelen-Tudos and Mao-Huglin methods. Individually, as well as the average of all the methods revealed that the monomer reactivity ratios of tetrahydrofurfuryl methacrylate were higher than isobornyl methacrylate. The dyad sequence distribution and dyad sequence lengths were calculated using the Igarashi and Pyun method and the sequence length distribution for tetrahydrofurfuryl methacrylate was observed to be higher with an increase in its feed content. This supports the reactivity ratio studies that a higher monomer reactivity ratio value for tetrahydrofurfuryl methacrylate was observed as compared to its comonomer. The thermal studies showed that the glass transition temperatures of the copolymers increased with an increase in isobornyl methacrylate content.
Keywords: Copolymer; methacrylates; micro structure; photocopolymerization; reactivity ratios; thermal studies

Synthesis of novel silica-polyimide nanocomposite films using aromatic-amino modified silica nanoparticles: mechanical, thermal and morphological investigations - Ghorpade, Ravindra V.; Rajan, C. R.; Chavan, Nayaku; Ponrathnam, S. (Express Polymer Letters, 2015)
Silica nanoparticles were modified with aromatic amino groups and modified-silica/polyimide composite films were prepared using them. 3,3!, 4,4!-Benzophenone tetracarboxylic dianhydride (BTDA) and 4,4!-oxydianiline (ODA) were used as precursors for polyimide matrix. The structures of the modified nanoparticles and hybrid nanocomposites were identified using Fourier Transform Infrared (FTIR) spectrometry. The hybrid composite films were evaluated for mechanical, thermal and morphological characteristics. Morphological results describe a uniform dispersion of silica particles in the polymer matrix. The thermal stability and mechanical properties of polyimide composite were improved, and the decomposition temperature was increased when the amount of silica nanoparticles was increased.
Keywords: hybrid polyimide composites; mechanical properties; Nanocomposites; nanoparticle modification; Thermal properties

Adsorption of strontium (II) metal ions using phosphonate-functionalized polymer - Bhosle, S. M.; Ponrathnam, S.; Tambe, S. S.; Chavan, N. N. (Bulletin of Materials Science, 2016)
Diethyl[3-(methoxydimethylsilyl)propyl]phosphonate (DMPP) polymer was synthesized for the strontium (II) metal ion recovery using diethylallylphosphonate as staring material. Diethylallylphosphonate was reacted with poly(methylhydro)siloxane (MW 1900-2000 g mol (-1) ) in the presence of Speier's catalyst. The synthesized monomer was characterized by IR, (1) H NMR, (1 3) C NMR and FT-IR spectroscopy techniques, and the synthesized polymers were characterized by IR and NMR spectroscopy, differential scanning calorimetry, thermogravimetric analysis and solubility. The synthesized polymer was used for sequestering strontium metal from the aqueous solution. The metal binding was examined by the energy dispersive spectroscopy and scanning electron microscopy for the adsorbed Sr(II). Batch adsorption studies were performed by varying three parameters, namely initial pH, adsorbent dose and the contact time. The reaction kinetics was determined by the Langmuir, Freundlich, and pseudo-first- and second-order models. Results of this study indicate that the synthesized polymer DMPP has been effective in removing Sr(II) from the aqueous solution.

Inverse high internal phase emulsion polymerization (i-HIPE) of GMMA, HEMA and GDMA for the preparation of superporous hydrogels as a tissue engineering scaffold - Nalawade, Archana C.; Ghorpade, Ravindra V.; Shadbar, Sadiqua; Qureshi, Mohammed Shadbar; Chavan, Nayaku; Khan, Ayesha A.; Ponrathnam, S. (Journal of Materials Chemistry B, 2016)
A series of novel superporous hydrogels for regenerative medicine were prepared by oil-in-water (o/w) or inverse high internal phase emulsion (i-HIPE) copolymerization of glycerol monomethacrylate (GMMA), 2-hydroxy ethyl methacrylate (HEMA) and glycerol dimethacrylate (GDMA) as a cross-linker using a non toxic solvent and a redox initiator system at the physiological temperature (37 degrees C). The monomer GMMA was synthesized from glycidyl methacrylate (GMA) by an alternative facile method using Amberlyst-15. The described i-HIPEs showed a significantly wider stability window. The polyHIPE hydrogels were characterized by FTIR, BET method for surface area, mercury porosimetry, SEM, DSC, TGA, XRD, compressive strain and strain recovery. The swelling ratio of the hydrogels and their degradation in 0.007 M NaOH and lipase B (Candida antarctica) solutions were determined gravimetrically and the rate of degradation was explained in terms of the molecular structure of the hydrogels. The morphological studies showed that the pore diameter varied between 20 and 30 mu m and the pore throats (interconnecting windows) diameter was in the range of 4-8 mu m. The described polyHIPE hydrogels were found to have an open cell morphology and interconnected pore architecture, which are important characteristics for scaffold applications. The initial cytotoxicity study performed according to ISO-10993-5 indicated cytocompatibility (97% cell viability) and the subsequent cell seeding and proliferation study exhibited 55-88% cell viability (increased monotonously from GHG-1 to GHG-5), which could be attributed to modulation of the physical and chemical properties of the hydrogels. The described super porous hydrogels are considered as potential candidates for scaffold materials in tissue engineering applications.

Prediction of reactivity ratios in free radical copolymerization from monomer resonance-polarity (Q-e) parameters: genetic programming-based models - Shrinivas, K.; Kulkarni, Rahul P.; Shaikh, Saif; Ghorpade, Ravindra V.; Vyas, Renu; Tambe, Sanjeev S.; Ponrathnam, S.; Kulkarni, Bhaskar D. (International Journal of Chemical Reactor Engineering, 2016)
The principal deficiency of the widely utilized Alfrey-Price (AP) scheme for computing reactivity ratios in the widely used free radical copolymerization is that it ignores important factors, such as the steric effects. This often leads to inaccurate reactivity ratio predictions by AP model. Accordingly, in this study, exclusively data-driven, Q-e parameter-based new models have been developed for the reactivity ratio prediction in free radical copolymerization. In the model development, a novel artificial intelligence formalism known as ``genetic programming (GP)'' that performs symbolic regression has been employed. The GP-based models possess a different functional form than AP model. Further, parameters of GP-based models were fine-tuned using Levenberg-Marquardt (LM) nonlinear regression method. A comparison of AP, GP and GP-LM as well as artificial neural network (ANN)-based models indicates that GP and GP-LM models exhibit superior reactivity ratio prediction accuracy and generalization performance (with correlation coefficient magnitudes close to or greater than 0.9) when compared with AP and ANN models. The GPbased reactivity ratio prediction models developed here due to their higher accuracy and generalization capability have the potential of replacing the widely used AP models.
Keywords: Alfrey-Price scheme; free radical copolymerization; genetic programming; reactivity ratio; symbolic regression

Removal of arsenite [As(III)] and arsenate [As(V)] ions from wastewater using TFA and TAFA resins: computational intelligence based reaction modeling and optimization - Patil-Shinde, V.; Mulani, K. B.; Donde, K.; Chavan, N. N.; Ponrathnam, S.; Tambe, S. S. (Journal of environmental chemical engineering, 2016)
Being significantly toxic, removal of arsenic forms an important part of the drinking- and waste-water treatment. Tannin is a polyphenol-rich substrate that efficiently and adsorptively binds to the multivalent metal ions. In this study, tannin-formaldehyde (TFA) and tannin-aniline-formaldehyde (TAFA) resins were synthesized and employed successfully for an adsorptive removal of arsenite [As(III)] and arsenate [As(V)] ions from the contaminated water. Next, a computational intelligence (CI) based hybrid strategy was used to model and optimize the resin-based adsorption of As(III) and As(V) ions for securing optimal reaction conditions. This strategy first uses an exclusively reaction data driven modeling strategy, namely, genetic programming (GP) to predict the extent (%) of As(III)/As(V) adsorbed on TFA and TAFA resins. Next, the input space of the GP-based models consisting of the reaction condition variables/parameters was optimized using genetic algorithm (GA) method; the objective of this optimization was to maximize the adsorption of As(III) and As(V) ions on the two resins. Finally, the sets of optimal reaction conditions provided by GP-GA hybrid method were verified experimentally the results of which indicate that the optimized conditions have lead to 0.3% and 1.3% increase in the adsorption of As(III) and As(V) ions on TFA resin. More significantly, the optimized conditions have increased the adsorption of As(III) and As(V) on TAFA resin by 3.02% and 12.77%, respectively. The GP-GA based strategy introduced here can be gainfully utilized for modeling and optimization of similar type of contaminant-removal processes.

Synthesis and characterization of thermally stable polyimides with a pendent phenothiazine unit based on new diamine 10-(3,5-diaminobenzoyl)phenothiazine - Ghorpade, Ravindra V.; Thorave, Asmita K.; Rajan, C. R.; Chavan, Nayaku; Ponrathnam, S. (High Performance Polymers, 2016)
A novel diamine 10-(3,5-diaminobenzoyl)phenothiazine (DBPT) with a side chain containing phenothiazine unit was synthesized. A new family of polyimides (PIs) containing phenothiazine unit in the side chains has been successfully synthesized by direct polycondensation of DBPT with pyromellitic dianhydride, 3,3',4,4'-benzophenone tertacarboxylic dianhydride, and 4,4'-oxydiphthalic anhydride (ODA) via a conventional two-step chemical imidization process. The yield of polymers was good enough, which were soluble in most organic solvents. The molecular orbital energy gaps, thermal stability, and crystallinity of PIs were investigated by molecular modeling, thermogravimetric analysis, and wide-angle X-ray scattering, respectively. Thermal properties of polymers were good enough to permit the use of these PIs in various applications; only 49% weight loss is detected at 900 degrees C in nitrogen atmosphere. X-Ray diffraction clearly reveals the amorphous nature of PIs. A quantum modeling study (density functional theory) has shown the influence of dianhydride structure on the energy difference of highest occupied molecular orbital and lowest unoccupied molecular orbital energy levels.
Keywords: phenothiazine-containing diamine; Polyimide; thermally stable polymer